Interrelation between Assessments of Child-Parental Interaction and Coping Strategies of “Most at Risk” Adolescents - Matafonova, S.I.; Rerke, V.; Krotova, T. (Psihologiâ i pravo, 2022)
The article presents a theoretical and an empirical research of problems of coping behavior among most at risk adolescents; it describes the interrelation between assessments of child-parental interaction and coping strategies of most at risk adolescents. The 41 teenagers from the “risk group” aged from 12 to 16, studying in 7-10 classes of different educational organizations in Irkutsk took part in this research. The “Method of primary diagnosis and identification of children from the “risk group” (M.I. Rozhkov, M.A. Kovalchuk), the questionnaire “Coping Strategies” (R. Lazarus) and the questionnaire “Parent-Child Interaction” (I.M. Markovskaya) were used in our research. The authors identified that most at risk adolescents show the coping strategies of emotional distancing from the problem situation; they rarely seek for support and understanding from parents. Ineffective child-parental interaction appears in the lack of self-control in adolescents. The obtained results made a conclusion that it is necessary to carry out the psychoeducational correctional work in order to harmonize the child-parental interrelation between most at risk adolescents and their parents, and to make constructive coping strategies and self-discipline. The article is intended for teachers-psychologists and psychologists-consultants. В статье представлено теоретическое и эмпирическое исследование проблем совладающего поведения подростков «группы риска», описана взаимосвязь оценок детско-родительского взаимодействия и копинг-стратегий подростков «группы риска». В исследовании приняли участие 41 подросток «группы риска» обучающихся 7—10 классов образовательных организаций г. Иркутска, в возрасте от 12 до 16 лет. Использовались «Методика первичной диагностики и выявления детей «группы риска» (М.И. Рожков, М.А. Ковальчук), Опросник копинг-стратегий» (Р. Лазаруса), опросник «Взаимодействие “родитель—ребенок”» (И.М. Марковская). Авторами выявлено, что подростки «группы риска» демонстрируют копинг-стратегии эмоционального дистанцирования от проблемных ситуаций, реже ищут поддержку и понимание со стороны родителей. Неэффективное детско-родительское взаимодействие появляется в отсутствии самоконтроля у подростков. Полученные результаты позволили сделать вывод о необходимости проведения психолого-педагогической коррекционной работы по гармонизации детско-родительского взаимодействия подростков «группы риска» и их родителей, формирования конструктивных копинг-стратегий и самоконтроля поведения. Статья предназначена педагогам-психологам, психологам-консультантам.